2007
DOI: 10.2174/092986707780059643
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Gestational Diabetes Mellitus

Abstract: About 2-5% of all pregnant women develop gestational diabetes mellitus (GDM) during their pregnancies and the prevalence has increased considerably during the last decade. GDM is a heterogeneous disorder that is defined as carbohydrate intolerance with onset or first recognition during pregnancy. It is manifested when pancreatic beta cells are no longer able to compensate for the increased insulin resistance during pregnancy, but the pathogenesis of the disease is still largely unknown. GDM is considered to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 206 publications
(276 reference statements)
2
72
0
5
Order By: Relevance
“…Gestational diabetes mellitus is a heterogeneous disorder where genetic and environmental factors interact to cause the disease [1,2]. Studies have demonstrated that gestational diabetes mellitus shares some genetic and phenotypic features with other types of diabetes such as type 1, type 2 and MODY [1,2].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Gestational diabetes mellitus is a heterogeneous disorder where genetic and environmental factors interact to cause the disease [1,2]. Studies have demonstrated that gestational diabetes mellitus shares some genetic and phenotypic features with other types of diabetes such as type 1, type 2 and MODY [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that gestational diabetes mellitus shares some genetic and phenotypic features with other types of diabetes such as type 1, type 2 and MODY [1,2]. However, different risk alleles/genes might be operative in different types of diabetes and gestational diabetes mellitus due to the heterogeneous nature of these disorders.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations